Design and synthesis of plasticizing fillers based on zirconium phosphonates for glycerol-free composite starch films - Marco Taddei (Journal of Materials Chemistry, 2012)
Novel starch-based composite films were prepared by solution casting from gelatinized starch, using a new class of layered zirconium hydroxyalkyl aminophosphonates, ZrF(O3PCH2)2NH(CH2)nOH (n = 3, 4, 5), as fillers/plasticizers. These compounds were specifically designed and synthesized for this application in order to support organic polar groups, able to interact with the polymer, on robust inorganic layers. Their structures were solved ab initio from powder X-ray diffraction data. The films, loaded with 2 wt% of fillers, were studied by means of various techniques such as X-ray diffraction, scanning and transmission electron microscopy, thermogravimetry, and stress–strain tests. The obtained results highlighted the double role played by the fillers as a reinforcement for the polymer matrix and as plasticizing agents: the composites showed improved thermal and mechanical properties, along with a significant reduction of volume swelling, if compared with the glycerol-plasticized films.